Cotton fabric dyeability assessment of floral extracts obtained from binary mixtures of Callistemon citrinus and Tagetes erecta L. Issue 4 (19th May 2019) - Sarwar, Mubashra; Ali, Shaukat; Hussain, Muhammad Tahir; Atif, Muhammad; Majeed, Muhammad Irfan
ABSTRACT: Parameters affecting extraction of natural colorants from five binary mixtures of floral parts of Callistemon citrinus and Tagetes erecta L., like ratio of each flower in the binary mixture of powdered floral parts, amount of powdered binary mixture to liquor ratio and extraction time, were optimized for dyeing of cotton fabric. Optimum dyeing was obtained at 60°C with 70 g/L exhausting agent (Na2 SO4 ), material to liquor ratio of 1:50 along with dyeing time of 100 min. The dyed fabric revealed good anti-bacterial activity and excellent ultraviolet protection factor (UPF).